Gender differences in adherence to COVID-19 preventative measures and preferred sources of COVID-19 information among adolescents and young adults with cancer. (April 2022) - Yan, Adam P.; Howden, Kaitlyn; Mahar, Alyson L.; Glidden, Camille; Garland, Sheila N.; Oberoi, Sapna
Abstract: Background: The COVID-19 pandemic has greatly altered the behavior of adolescents and young adults (AYAs) with cancer. No data exists on how gender influences the adherence of individuals with cancer to COVID-19 related public health guidelines and their preferred methods of receiving COVID-19 related information. Methods: We conducted a cross-sectional survey of adolescents and young adults with cancer. Data were summarized using descriptive statistics. Multiple logistic regression was used to assess differences in adherence to COVID-19 preventative behaviors, and differences in preferred information sources of COVID-19 related information between men and women. Results: Among 633 participants, adherence to key COVID-19 preventative measures was 44.9-58.8% for males and 53.4-68.1% for females. After adjusting for key confounding variables in multivariable analysis, males were less likely to adhere to frequent hand washing (AOR [adjusted odds ratio] 1.45, 95% CI [confidence interval] 1.03-2.03), not touching face (AOR 1.82, 95% CI 1.29-2.56) and social distancing (AOR 1.93, 95% CI 1.37-2.71) than females. Both genders preferred to receive information from their cancer institutes and social media. Discussion: Gender-specific interventions are needed to improve the adherence of males to COVID-19 precautionary measures. Information should be disseminated via cancer institutes and social media as these are the preferred sources of COVID-19 related information among AYAs with cancer. Graphical Abstract: ga1 Highlights: Adherence to COVID-19 precautionary measures is poor for both men and women. Males are less likely to adhere to COVID-19 precautionary measures. Both men and women prefer information from their cancer institutes and from social media.